SUBSTITUSI PUREE KURMA (Phoenix Dactylifera L.) TERHADAP DODOL MELAYU - Safitriani, Nadia Sarmanisa; Agung Arif Gunawan; Rosie Oktavia Puspita Rini; Silitonga, Frangky (Sekolah Tinggi Pariwisata Sahid Surakarta, 2025)
This study aims to analyze substituting date puree (Phoenix dactylifera) as a sugar replacement in the production of dodol, based on hedonic test and hedonic quality test by panelists preferences. The research background based on the high consumption of added sugar, thus requiring healthier natural sweetener alternatives. The research method used an experimental design with three formulations: 0% date puree, 50% date puree, and 100% date puree. Organoleptic test were carried out by trained and semi-trained panelist, evaluating aspect of color, aroma, taste, and texture using a 1-5 hedonic scale. Analysis was performed using Kruskal-Wallis test. The analysis revealed that the 50% date puree formulation received the highest preference scores for taste and texture, while the 100% substitution produced a stronger color and aroma but was less favored by some panelists. These findings highlight that date puree can be effectively used as a natural sweetener in dodol with good consumer acceptance. This study expands to the innovation of Indonesian traditional food and supports healthier dietary patterns.